Gambaran Pengalaman Perempuan Korban Kekerasan Dalam Pacaran (KDP) Di Indonesia - Barenns, Dinda Audreya Azhari; Swandi, Ni Luh Indah Desira (Jurnal Ilmiah Wahana Pendidikan, 2023)
Dating violence is a phenomenon that is increasingly occurring in intimate relationships, especially at the early stage of adolescence. Approximately 1 in 4 or 26.4% of women in Indonesia have experienced violence physically, verbally, sexually, emotionally, and financially. Although anyone can experience dating violence, women tend to be victims more often than men. Violence against women stems from the imbalance of power relations between women and men that has developed over a long time ago resulting in a culture called patriarchy. This study aims to explore the experiences of women who have been or are currently being the victims of dating violence. The research is conducted to 20 females aged 19-30 years who live in Bali and Java Island. This study uses descriptive qualitative research methods and is analyzed using thematic analysis method. The results of the study found that 100% of respondents had experienced verbal violence, 55% had experienced physical violence, 40% had experienced sexual violence, and 25% had experienced financial violence. However, as many as 17 out of 20 respondents had blamed themselves for the violence they had experienced. The results showed that there were differences in perceptions of the dating violence experience, the level of self-esteem, and their ability to forgive among the respondents.